2017
DOI: 10.3892/or.2017.5460
|View full text |Cite
|
Sign up to set email alerts
|

ADAM9 functions as a promoter of gastric cancer growth which is negatively and post-transcriptionally regulated by miR-126

Abstract: A disintegrin and metalloproteinase domain 9 (ADAM9) is a membrane-anchored protein implicated in cell-cell and cell-matrix interactions, including the process of tumorigenesis. However, the role of ADAM9 in gastric cancer (GC) has not been clearly illustrated. In the present study, we found aberrant overexpression of ADAM9 in both GC tissues and cell lines. The expression of ADAM9 was significantly correlated with patient clinicopathological features including tumor size, local invasion, lymph node metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
0
15
0
2
Order By: Relevance
“…In addition, using RNA-seq based transcriptome profiling we compared down-regulated genes with in silico target prediction and identified 10 candidate genes. Interestingly, results from literature research showed that 6 of the genes ( ADAM9, PLK2, CAMSAP1, PTPN9, EGFL7 and SLC7A5 ) have been demonstrated as the functional targets of miR-126 (23, 3442), suggesting the relevance of our analysis. To identify the GCT-relevant target of miR-126, we screened all the 10 candidate genes in KGN cells by RNAi.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, using RNA-seq based transcriptome profiling we compared down-regulated genes with in silico target prediction and identified 10 candidate genes. Interestingly, results from literature research showed that 6 of the genes ( ADAM9, PLK2, CAMSAP1, PTPN9, EGFL7 and SLC7A5 ) have been demonstrated as the functional targets of miR-126 (23, 3442), suggesting the relevance of our analysis. To identify the GCT-relevant target of miR-126, we screened all the 10 candidate genes in KGN cells by RNAi.…”
Section: Discussionmentioning
confidence: 85%
“…The roles of ADAM9 in different types of cancers have been discussed in many previous works. Caporali et al suggested that microRNA‐126‐3p may contribute to the dabrafenib resistance of melanoma via up‐regulating ADAM9 Caporali; Oria et al found that ADAM9 may contribute to the development of pancreatic ductal adenocarcinoma; Dong et al demonstrated that ADAM9 can induce the epithelial‐mesenchymal transition of the hepatoma cells; Wang et al suggested that ADAM9 functions as an oncogene in gastric cancer, and it was negatively regulated by micoRNA‐126 . A study on the roles of ADAM9 in OC is limited.…”
Section: Discussionmentioning
confidence: 99%
“…A disintegrin and metalloproteinase 9 is a member of the ADAM families, and the roles of ADAM9 in different types of cancers have been discussed previously. [12][13][14] In the case of OC, ADAM9 was found to be up-regulated in tumor tissue than the normal tissue 15 ; however, the underlying mechanism is still unclear. In the present study, we will examine expression of ADAM9 in human OC tissue by immunohistochemistry and RT-qPCR method and investigate potential diagnostic and prognostic value of ADAM9 for OC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Located at chromosome 9q34.3, an intron of EGF-like domain-containing protein 7 (EGFL7), miRNA (miR)-126 is associated with various human tumors (19). Commonly exhibiting tumor suppressive properties, miR-126 is expressed at a low level in numerous human malignances, including lung cancer (20), colon cancer (21), breast cancer (22), osteosarcoma (23) and gastric cancer (24). Repression of cancer cell proliferation (25), migration (26) and invasion (27) mediated by miR-126 can be achieved via targeting specific oncogenes, including phospoinositide 3-kinase, V-Ki-ras2 Kirsten rat sarcoma viral oncogene, EGFL7 and vascular endothelial growth factor (VEGF).…”
Section: Introductionmentioning
confidence: 99%